Development and evaluation of multigrain pasta - Laxmi Verma; N. K. Mishra (International Journal of Nutritions, 2025)
Pasta is one of the most consumed food among the food products prepared from cereals due to low cost, ease in preparation along with pleasant textural and sensory characteristics. This study was performed to prepare multigrain pasta by utilising the numerous health benefits of wheat, chickpea, kodo and ragi flour. Each ingredient was selected according to unique nutritional attributes which will be incorporated in pasta to make it more nutritious than traditional pasta prepared by refined wheat flour. Ingredients were ground and flours were separated according to the particle size 200-300 µm, 400-500 µm and 500-600 µm and mixed at the rates of 40:30:20:10 respectively. Guar gum (1%, 2% and 3%) was mixed to reduce the cooking loss during cooking. Pasta was prepared using homemade pasta maker machine with two different sheet thickness of 0.8 mm and 1.4 mm. Total 18 samples were obtained after combining all the treatments. The effects of particle size of flour (FPS), amount of guar gum (GG) and sheet thickness (ST) on different cooking qualities of multigrain pasta were studied. It was observed that pasta prepared from FPS of 400-500 µm obtained maximum sensory score during sensory evaluation also pasta prepared from FPS of 400-500 µm using 2% GG with 0.8 mm sheet thickness obtained maximum sensory score of 8.80 in terms of overall acceptability. Also it was observed that pasta prepared from FPS of 200-300 µm were found to be sticky whereas pasta prepared from FPS of 500-600 µm were disintegrated after cooking.
Keywords: ANOVA; CRD; Multigrain pasta; Pasta; WAI